Attitudes and perceptions about COVID‐19 vaccination in the population with chronic HIV infection: A systematic review - Emilia Afonso López Shirley; Jover‐Diaz Francisco; Delgado Sánchez Elisabet; Gea Velázquez de Castro Teresa; Bernabéu Martínez María (Health Science Reports, 2023)
Abstract Background and Aims The coronavirus disease 2019 (COVID‐19)‐infected population has been increasing during the last 3 years worldwide. Moreover, simultaneously, COVID‐19 vaccine clinical trials were launched. By the end of 2020, the Food and Drug Administration had authorized the emergency use of two messenger RNA vaccines against COVID‐19. These fast‐track vaccine approvals have produced controversy about their safety and efficacy. The purpose of this research was to discover attitudes and perceptions regarding vaccination against COVID‐19 disease among vulnerable groups such as human immunodeficiency virus (HIV)‐infected patients. Methods Between June 2, 2021 and March 4, 2022, we conducted a cross‐sectional study through a survey of high‐risk patients with severe COVID‐19, such as HIV‐infected patients in the Infectious Diseases Unit (Hospital Clínico Universitario San Juan, Alicante). For the data collection strategy, a nonprobabilistic snowball sampling was adopted. A structured, anonymous, self‐administered questionnaire was developed in which questions and statements were designed to evaluate their attitudes and perceptions about COVID‐19 vaccination. Descriptive and bivariate analyses were performed for the obtained data. Results Forty‐eight participants were recruited with a mean age of 51.5 ± 11.9 years. Thirty‐nine of them (81.3%) were male. The acceptance rate of COVID‐19 vaccination was extremely high (95.7%). Bivariate analysis showed older patients significantly received a higher proportion of vaccine doses at the time of the survey (p = 0.047). Older patients were more aware of the vaccine safety controversy (61.1%) compared to younger patients (p = 0.054). There were no other significant differences between groups among questions regarding safety, efficacy, or attitudes about COVID‐19 vaccination. Conclusion An extremely high degree of acceptance for COVID‐19 vaccination was reported. Older patients were more aware of the vaccine safety controversy. Medical staff is the most trustworthy source of information, far above all other sources. Social networks and opinion leaders have not been shown to significantly influence our population.